2010
DOI: 10.1177/0961203310372938
|View full text |Cite
|
Sign up to set email alerts
|

Primary antiphospholipid syndrome in premenopausal women: low vitamin D, high fat mass and maintained bone mineral mass

Abstract: The aim of this study was to analyze vitamin D levels and their association with bone mineral density and body composition in primary antiphospholipid syndrome. For this cross-sectional study 23 premenopausal women with primary antiphospholipid syndrome (Sapporo criteria) and 23 age- and race-matched healthy controls were enrolled. Demographic, anthropometric, clinical and laboratorial data were collected using clinical interview and chart review. Serum 25-hydroxyvitamin D levels, parathormone, calcium and 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
2
23
0
1
Order By: Relevance
“…VitD levels above 30 ng/ ml were considered sufficient, according to international guidelines. 10 Insufficiency was defined as values between 10 and 30 ng/ml and deficiency when values fell below 10 ng/ml.…”
Section: Liaisonmentioning
confidence: 99%
See 1 more Smart Citation
“…VitD levels above 30 ng/ ml were considered sufficient, according to international guidelines. 10 Insufficiency was defined as values between 10 and 30 ng/ml and deficiency when values fell below 10 ng/ml.…”
Section: Liaisonmentioning
confidence: 99%
“…[9][10][11][12] In all studies, the average value for APS patients was below 30 ng/ml, a cut-off value suggested by international guidelines. 13 Although they lack data on race, seasonality, nutrition and sun exposure, overall these studies suggest that APS patients are comparably as affected by hypovitaminosis D as they are by other systemic autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…23,28 Regarding body composition, fat mass was a relevant factor for hypovitaminosis D in autoimmune diseases. 29 In Juvenile onset SLE (JoSLE) there is no data regarding the influence of vitamin D status in bone health and the risk of deficiency was recently demonstrated to be higher in autoimmune conditions. 30 Moreover, glucocorticoid (GC) may have a regulatory effect on vitamin D metabolism 31 aggravating this deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Conflicting reports were published about the association of osteoporosis to APS, 20,21 but the more common conclusion was that longstanding anticoagulation in APS patients is an indirect risk factor to develop osteoporosis, 21,22 possibly related to the consequential vitamin D deficiency in anticoagulated APS patients. 21 Among many of the above-mentioned reports, the most striking piece of evidence suggesting a strong link between APS and its orthopedic complications is the symptomatic and radiologic improvement upon initiation of anticoagulation.…”
Section: Known Orthopedic Manifestations Of Apsmentioning
confidence: 99%